Analisis Atribut Kepemimpinan Di SMP ST. Lusia Siborongborong - Meli Afriani N; Ririn Simanjuntak; Ibelala Gea (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
This study aims to find out how the leadership attributes are applied in SMP ST. Lucia Siborongborong. The method used is descriptive qualitative through literature studies and also direct interviews to ST Middle School. Lucia Siborongborong. The conclusion is that leadership attributes are very important for a leader to have, such as capacity, achievement, responsibility, participation, and status. Capacity here includes intelligence, alertness or accuracy, verbal fluency, the ability to judge and make decisions and originality. Achievement attributes include knowledge, academic achievement, achievement in sports. A leader must also have a sense of responsibility in the form of independence, full of initiative, diligent, aggressive, and confident. Participation attributes such as being able to socialize, being able to work together, and being able to adapt. Then status is socioeconomic status. Even though they don’t always have a higher socio-economic leader status than those who are led. The above attributes differ according to the type of organization